1998
DOI: 10.1136/thx.53.9.744
|View full text |Cite
|
Sign up to set email alerts
|

Asthma control during long term treatment with regular inhaled salbutamol and salmeterol

Abstract: Background-The adverse eVects of long term treatment of asthma with the short acting agonist fenoterol have been established in both epidemiological and clinical studies. A study was undertaken to investigate the eYcacy and safety of long term treatment with salbutamol and salmeterol in patients with mild to moderate bronchial asthma. Methods-In a two centre double dummy crossover study 165 patients were randomly assigned to receive salbutamol 400 µg qid, salmeterol 50 µg bid, or placebo via a Diskhaler. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
93
2
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(98 citation statements)
references
References 31 publications
2
93
2
1
Order By: Relevance
“…Similarly, the current study found that asthmatics who were not taking LABA, but were taking ICS and could be classified as mild persistent asthma were the most variable, with highest baseline Rrs SD and greatest decrease in Rrs SD with BD. In contrast, subjects that received LABA with corticosteroids and could be classified as moderate persistent asthmatics had the lowest baseline Rrs SD of the asthma subjects and the smallest decrease with BD, perhaps indicating that LABA may contribute to reduced variability similar to reduced exacerbations reported in some other studies [45,46]. While a prospective study is needed to confirm a relationship of short-term variation in Rrs to long-term variation in airway function and symptoms, this may be important, especially since it has been recently shown that fluctuation analysis of variation in airway function can predict the risk of asthma exacerbations [8].…”
Section: Effect Of a Bdmentioning
confidence: 51%
See 1 more Smart Citation
“…Similarly, the current study found that asthmatics who were not taking LABA, but were taking ICS and could be classified as mild persistent asthma were the most variable, with highest baseline Rrs SD and greatest decrease in Rrs SD with BD. In contrast, subjects that received LABA with corticosteroids and could be classified as moderate persistent asthmatics had the lowest baseline Rrs SD of the asthma subjects and the smallest decrease with BD, perhaps indicating that LABA may contribute to reduced variability similar to reduced exacerbations reported in some other studies [45,46]. While a prospective study is needed to confirm a relationship of short-term variation in Rrs to long-term variation in airway function and symptoms, this may be important, especially since it has been recently shown that fluctuation analysis of variation in airway function can predict the risk of asthma exacerbations [8].…”
Section: Effect Of a Bdmentioning
confidence: 51%
“…Also, the distinction of severity is problematic once treatment is initiated and some of the differences observed may be due more to therapy than to severity. Indeed, in a 20-month cross-over study by TAYLOR et al [45], asthma symptoms and variation in PEFR were higher in asthmatic subjects receiving SABA compared with subjects receiving a LABA. Similarly, the current study found that asthmatics who were not taking LABA, but were taking ICS and could be classified as mild persistent asthma were the most variable, with highest baseline Rrs SD and greatest decrease in Rrs SD with BD.…”
Section: Effect Of a Bdmentioning
confidence: 99%
“…A reduced exacerbation frequency was one of the major findings of studies combining inhaled steroid with long-acting b 2 -agonists [2,21]. As asthma exacerbations may be initiated at the epithelial level by secretion of chemokines and growth factors, it was the study9s objective to investigate some of these aspects in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been adopted because of the inflammatory nature of asthma and because, somewhat controversially, regular use of shortacting b 2 -agonists at best confers no distinct benefit on overall asthma control [2], and at worst may cause a deterioration [3].A number of possible mechanisms have been proposed to explain the adverse effects of chronic short-acting b 2 -agonist therapy [4], but the debate continues. One possible explanation currently under consideration is related to the fact that b 2 -agonists are chiral and are administered as racemic mixtures of a pharmacologically active eutomer (e.g.…”
mentioning
confidence: 99%
“…This approach has been adopted because of the inflammatory nature of asthma and because, somewhat controversially, regular use of shortacting b 2 -agonists at best confers no distinct benefit on overall asthma control [2], and at worst may cause a deterioration [3].…”
mentioning
confidence: 99%